2021
DOI: 10.3389/fmed.2021.696153
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Predicts Poor Prognosis of Patients After Percutaneous Coronary Intervention: A Meta-Analysis of Cohort Studies

Abstract: Background: Frailty has been related to a higher risk of cardiovascular events, while the association between frailty and outcomes for patients with coronary artery disease (CAD) after percutaneous coronary intervention (PCI) remains unclear. We performed a meta-analysis of cohort studies to evaluate the above association.Methods: Cohort studies aiming to determine the potential independent association between frailty and clinical outcomes after PCI were identified by search of PubMed, Embase, and Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although the observational study design cannot account for unmeasured confounders, it is nonetheless notable that the study groups were not statistically different across predictors of poor PCI outcomes in older adults, including frailty. 27 , 28 Therefore, the baseline characteristics between PCI groups suggest that simple differences in comorbid disease burden are unlikely to be the culprit. Furthermore, the risk of all‐cause death was actually amplified in adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observational study design cannot account for unmeasured confounders, it is nonetheless notable that the study groups were not statistically different across predictors of poor PCI outcomes in older adults, including frailty. 27 , 28 Therefore, the baseline characteristics between PCI groups suggest that simple differences in comorbid disease burden are unlikely to be the culprit. Furthermore, the risk of all‐cause death was actually amplified in adjusted analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by He et al [ 40 ] in 2022, with nine studies and a cohort of 2658 patients, showed that the occurrence of frailty was between 12.5% and 27.8% and correlated with higher in-hospital [odds ratio (OR) = 3.59, 95%CI: 2.01-6.42, I 2 = 35%], short-term (OR = 6.61, 95%CI: 2.89-15.16, I 2 = 0%), as well as long-term mortality (HR = 3.24, 95%CI: 2.04- 5.14, I 2 = 70%) of PCI patients. A meta-analysis by Wang et al [ 41 ] in 2021 demonstrated an independent positive association of frailty and all-cause mortality (adjusted RR = 2.94, 95%CI: 1.90–4.56, I 2 = 56%, P < 0.001) and MACEs (adjusted RR = 2.11, 95%CI: 1.32–3.66, I 2 = 0%, P = 0.002). Similarly, a meta-analysis of six studies by Yu et al [ 42 ] in 2023 reported higher rates of all-cause mortality (HR= 2.29, 95%CI: 1.65–3.16, P = 0.285), rehospitalization (HR = 2.53, 95%CI: 1.38–4.63), and in-hospital major bleeding (HR = 1.93, 95%CI: 1.29–2.90, P = 0.825) in PCI cohort.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Frailty is consistently found to be related to poor outcomes of numerous cardiovascular conditions and procedures. 21,22 Among methods for its assessment, the frailty phenotype collects data that may not be readily available, the frailty index requires a multidisciplinary team, and the clinical frailty scale (CFS) contains many impression-based components. [23][24][25] BI is widely used to evaluate physical functional ability, is easy to implement, and, with adequate training, has demonstrated very high reliability.…”
Section: Discussionmentioning
confidence: 99%